2009
DOI: 10.1534/genetics.109.103333
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Stochastic Switching Rates in Asymmetric Fitness Landscapes

Abstract: Uncertain environments pose a tremendous challenge to populations: The selective pressures imposed by the environment can change so rapidly that adaptation by mutation alone would be too slow. One solution to this problem is given by the phenomenon of stochastic phenotype switching, which causes genetically uniform populations to be phenotypically heterogenous. Stochastic phenotype switching has been observed in numerous microbial species and is generally assumed to be an adaptive bet-hedging strategy to antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
133
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(156 citation statements)
references
References 18 publications
23
133
0
Order By: Relevance
“…Increasing the variability parameter c (i.e. increasing the variance in waiting time) decreases the evolutionarily stable switching rate, which can then be orders of magnitude less than 1/n, consistent with previous results in the absence of spatial heterogeneity [15]. As the migration rate increases, the evolutionarily stable switching rate first decreases.…”
Section: (A) Description Of the Simulationsupporting
confidence: 90%
See 2 more Smart Citations
“…Increasing the variability parameter c (i.e. increasing the variance in waiting time) decreases the evolutionarily stable switching rate, which can then be orders of magnitude less than 1/n, consistent with previous results in the absence of spatial heterogeneity [15]. As the migration rate increases, the evolutionarily stable switching rate first decreases.…”
Section: (A) Description Of the Simulationsupporting
confidence: 90%
“…Figure 3a illustrates the difference between results for the symmetric regime above (all selection coefficients equal) and this regime, in which higher migration rates select for higher switching rates. Consistent with single-deme theoretical results [15,16], asymmetry often leads to the evolution of zero mutation rate when the migration rate is low. As the level of asymmetry in selection within demes increases, the curves change from dipping to monotonically increasing with migration.…”
Section: (C) Migration Can Increase the Stable Switching Ratesupporting
confidence: 80%
See 1 more Smart Citation
“…This uninvadable switching rate is an evolutionary stable strategy (ESS) in an infinite population 60 . Further studies confirmed these results and also generalized them to include both environmental and spatial fluctuations in selection 40,54,61 . Most of these studies, however, consider the dynamics of mutation rates in infinite populations, and they do not explore the evolutionary fate of a new mutation in a finite population subject to demographic stochasticity.…”
Section: Discussionsupporting
confidence: 55%
“…Previous study of partly heritable phenotypic variation has been pursued in an infinite population 6,40,53,54 , with the notable exception of work by ref. 55 studied bet-hedging against rare events, whose analysis involved considering a single environmental change.…”
Section: Evolutionary Bet-hedging Modelsmentioning
confidence: 99%